Papel do DNA extracelular sobre a estrutura e resposta a antifúngicos em biofilmes de Trichosporon asahii e T. Inkin formados em meio simulador de urina e RPMI 1640 - Pereira, Lívia Maria Galdino (2022)
Fungi of the genus Trichosporon are part of the transient and resident microbiota of humans. However, depending on the immunological condition of the patients, such as in patients with hematological malignancies, these fungi can cause severe infections, which can lead to death in up to 90% of cases. Infections caused by Trichosporon spp. are usually associated with the formation of biofilms on medical devices, such as urinary foley probes and catheters. Biofilms are microbial communities strongly adhered to a surface, protected by a self-produced extracellular matrix, composed of water, proteins, lipids and extracellular DNA (eDNA). Although all these components are associated with the process of cell aggregation and adhesion to surfaces, the latter is more prominent. In addition, urinary tract infections are an anatomical site that are very affected by trichosporonosis, mainly by patients with hematological cancer, immunosuppressive diseases, neutropenia and HIV carriers. Thus, this study aimed to evaluate the influence of eDNA on formation and development, correlating with its sensitivity to antifungal agents. Additionally, the influence of DNAse on the sensitivity of mature biofilms formed in RPMI 1640 medium and urine simulating medium (MSU) was evaluated. Initially, biofilms were formed in a 96-well polystyrene plate from a cell suspension (106 cells/mL) for further analysis of biomass, metabolic activity, cell viability and eDNA release at times 6, 24 and 30 h. Then, the influence of adding eDNA (1280, 640, 320, 160 and 80 ng/mL) at different stages of biofilm formation (0, 6, 24 and 30 h) was evaluated, as well as the action of the enzyme DNAse (2, 1, 0.5 and 0.25 mg/mL) combined with amphotericin B (AMB 64 µg/mL for T. asahii and 8 µg/mL for T. inkin) and voriconazole (VRZ 64 µg/mL for both strains) on the structure and sensitivity of fungal biofilms. Secondly, biofilms formed on MSU and RPMI were compared regarding the addition of eDNA (160 ng/mL) after 24, 48 and 72 h of incubation and subsequent sensitivity to AMB and VRZ at the same concentrations above. The results demonstrated that T. asahii and T. inkin biofilms released eDNA as they increased metabolic activity and biomass as a function of time. The morphology and ultrastructure of biofilms were evaluated using scanning electron microscopy (SEM) and laser confocal microscopy. Biomass increased by up to 50% when eDNA was added to the medium, also evidenced by scanning electron microscopy images. Likewise, biofilms formed with exogenous eDNA became more tolerant to AMB and VRZ. In the treatment with DNAse (0.25 mg/mL) biofilms were obtained that were less robust and more sensitive to the antifungals tested, with cellular disaggregation being observed in the confocal microscopy images. It was also noticed that the Trichosporon strains tested were able to form a biofilm in MSU, evidenced by the biomass and electron microscopy compatible with growth in RPMI medium. In addition, biofilms pretreated with eDNA both had increased biomass (66% for T. asahii and 42% for T. inkin) and were more tolerant to antifungal agents in the MSU. Thus, it is concluded that eDNA is an essential component for several stages of the development of T. asahii and T. inkin biofilms, and may be a possible target for the development of antifungal strategies.